Organ shortage : ethics, law, and pragmatism / [edited by] Anne-Maree Farrell, David Price and Muireann Quigley. - Farrell, Anne-Maree, 1964-; Price, David P. T.; Quigley, Muireann (Cambridge law, medicine, and ethics ;, 2011)
Organ shortage is an ongoing problem in many countries. The needless death and suffering which have resulted necessitate an investigation into potential solutions. This examination of contemporary ethical means, both practical and policy-oriented, of reducing the shortfall in organs draws on the experiences of a range of countries. The authors focus on the resolution and negotiation of ethical conflict, examine systems approaches such as the 'Spanish model' and the US Breakthrough Collaboratives, evaluate policy proposals relating to incentives, presumed consent, and modifications regarding end-of-life care, and evaluate the greatly increased use of (non-heart-beating) donors suffering circulatory death, as well as living donors. The proposed strategies and solutions are not only capable of resolving the UK's own organ-shortage crisis, but also of being implemented in other countries grappling with how to address the growing gap between supply and demand for organs.